2023
DOI: 10.3390/en16145417
|View full text |Cite
|
Sign up to set email alerts
|

Syngas Production from Protective Face Masks through Pyrolysis/Steam Gasification

Abstract: The COVID-19 pandemic has caused a heavy expansion of plastic pollution due to the extensive use of personal protective equipment (PPE) worldwide. To avoid problems related to the entrance of these wastes into the environment, proper management of the disposal is required. Here, the steam gasification/pyrolysis technique offers a reliable solution for the utilization of such wastes via chemical recycling into value-added products. The aim was to estimate the effect of thermo-chemical conversion temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The model will seek to provide an understanding of emerging opportunities and their underlying challenges for solid waste management companies, and the applicability of the model will be demonstrated with a case study focusing on new markets for MSW's operations. An integrated analytical framework will also be applied to comparing the results with the recent literature [24]. However, several barriers [25] to the integration of the process model must first be identified including by using recommendations provided to develop integrated process models in other parts of Canada by policy makers wishing to facilitate the development of novel biomass or other paper waste in other parts of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…The model will seek to provide an understanding of emerging opportunities and their underlying challenges for solid waste management companies, and the applicability of the model will be demonstrated with a case study focusing on new markets for MSW's operations. An integrated analytical framework will also be applied to comparing the results with the recent literature [24]. However, several barriers [25] to the integration of the process model must first be identified including by using recommendations provided to develop integrated process models in other parts of Canada by policy makers wishing to facilitate the development of novel biomass or other paper waste in other parts of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Thermochemical conversion processes such as pyrolysis and gasification are one of the possible solutions to address the problems related to PW by upcycling it into valuable products. Many research studies have shown that PW are easily converted into gaseous or liquid energy and chemical products via the aforementioned processes [4][5][6][7]. When plastic thermally degrades, it releases high contents of volatile matter, consequently, the main products are VOC (volatile organic compounds), while the composition of evolved chemical species mainly depends on selected process conditions.…”
Section: Introductionmentioning
confidence: 99%